1977
DOI: 10.1038/bjc.1977.202
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance of caeruloplasmin and iron transferrin in blood of patients with various malignant diseases

Abstract: Summary.-Electron spin resonance studies have been made of caeruloplasmin and iron transferrin levels in whole blood of healthy controls and patients with a variety of malignant conditions receiving various forms of treatment.A small difference was found in caeruloplasmin level between normal males and females, although normal females receiving contraceptive steroids had an elevated level. No difference was found in iron transferrin level. Various conditions increased the caeruloplasmin and some also decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…There was no correlation between either metalloprotein and the total white-cell count, platelet count, haemoglobin or packed-cell volume. There was no sex difference in CLL patients, although a slight difference has been shown between normal males and females (Pocklington & Foster, 1977).…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…There was no correlation between either metalloprotein and the total white-cell count, platelet count, haemoglobin or packed-cell volume. There was no sex difference in CLL patients, although a slight difference has been shown between normal males and females (Pocklington & Foster, 1977).…”
Section: Methodsmentioning
confidence: 76%
“…(Markovitz et al, 1955) and in other malignancies (Fisher & Shifrine, 1978;Andrews, 1979). The significance of raised copper levels in malignancy has been debated (Pocklington & Foster, 1977).…”
mentioning
confidence: 99%
“…plasma, and serum are iron transferrin with a signal This value was estimated from a receiver-operating of g Å 4.2 and the copper ceruloplasmin with a signal of g Å 2.049 (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)14). In the pleural effusions, we also observed the signals with g Å 4.2 and 2.049.…”
Section: Origin Of Fe 3/ and Cu 2/ Signals From The Pleuralmentioning
confidence: 99%
“…nance (ESR) 1 method on blood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Some authors The peak-to-peak height was used as a measure of sighave reported that the patients with the malignant nal intensity, since the signal was confirmed to have diseases such as cancer and Hodgkin's disease had a constant line width and line shape in all the samples.…”
mentioning
confidence: 99%
“…E.s.r. provides a very rapid method for the measurement ofiron transferrin and an extension of thc method can be used to provide an estimatc of the total plasma transfcrrin concentration (Pocklington et a / , 1977). E.s.r.…”
Section: (A) Native Constituents Ofthe Bloodmentioning
confidence: 99%